Contrast induced nephropathy in patients with pre-existing renal impairment undergoing coronary angiogram and percutaneous transluminal coronary angioplasty. - Subedi, B; Siddique, MA; Zaman, SM; Hasan, MI; Arzu, J; Awal, A; Fatema, K (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2): 270-274 The abstract of this article is available on the PubMed website